Development of titanium diboride layer through superplastic compression method /Nor Taibah Taazim - Nor Taibah, Taazim (2016)
The aim of this work is to explore the possibility of combining boronizing and superplastic deformation on titanium alloy (Ti6Al4V) substrate. Superplastic boronizing (SPB) is carried out at three different temperatures of 1173 K, 1223 K, and 1273 K, and it is held for four different boronizing times of 1, 2, 3 and 6 hours. Titanium diboride (TiB2) is the only boride compound identified after the boronizing process. Boronized layer thickness in the range of 44.9 to 149.3 μm is formed on the surface of Ti6Al4V and the surface hardness values increase with the respect of the formation's degree of the hard boronized layer. Diffusion coefficient values attained for all temperatures are 1.44 x 10-13, 4.1 x 10-13 and 8.86 x 10-13 m2s-1 respectively and the values are higher as compared to other works referred. The activation energy obtained for this process is 226.17 kJmol-1. The results obtained suggest that the SPB process provides a more competent and efficient process for the formation of a boronized layer on the alloy.